Environmental Impact Assessment and Mitigation Strategies for WPCCN: Fostering Sustainable Development Through Technological and Policy Interventions - Lina Yuan; Huajun Chen; Jing Gong; Xianli Wen; Mingwei Kong (International Journal of Distributed Sensor Networks)
This study investigates the environmental impact of wireless-powered cooperative communication network (WPCCN) and proposes comprehensive mitigation strategies to achieve sustainable development. WPCCN, which utilizes wireless energy transmission to enhance communication coverage and efficiency, may pose environmental challenges such as increased electromagnetic radiation, higher energy consumption, and electronic waste generation. The research evaluates these impacts through a detailed assessment framework, considering electromagnetic radiation exposure, energy consumption throughout the device life cycle, and the overall carbon footprint. To mitigate these effects, the study proposes a range of strategies, including optimizing energy transfer efficiency, integrating renewable energy sources, developing environmentally friendly materials, and implementing robust environmental standards and green procurement policies. MATLAB simulations demonstrate that these strategies can significantly reduce the environmental footprint of WPCCN. Additionally, the study highlights the socioeconomic implications of deploying WPCCN, emphasizing the need for balanced strategies that maximize benefits while addressing potential challenges. Future research should focus on enhancing the accuracy of environmental impact assessments, developing advanced materials and designs, and creating adaptive policies to support the sustainable growth of WPCCN.